2021
DOI: 10.1097/mpa.0000000000001714
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism in Acute Necrotizing Pancreatitis

Abstract: Objectives Studies on the incidence of venous thromboembolism (VTE) in acute pancreatitis (AP) are scarce. We conducted a large database study to evaluate this relationship. Methods Data were extracted from a large electronic health record (Explorys; IBM Watson Health, Armonk, NY). We identified patients with AP in 2018 and 2019, analyzing VTE incidence at 30 days after diagnosis of AP. Univariate and multivariate analyses were performed to identify ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Many studies have found an increased risk of VTE among patients with inflammatory bowel disease 8,17,25–28 . Likewise, two studies identified positive associations of acute and chronic pancreatitis with VTE, respectively 29,30 . Our analysis additionally found some moderate associations of gastroesophageal reflux disease, gastritis and duodenitis, irritable bowel syndrome, diverticulum, non‐alcoholic fatty liver disease, and biliary diseases with VTE risk.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Many studies have found an increased risk of VTE among patients with inflammatory bowel disease 8,17,25–28 . Likewise, two studies identified positive associations of acute and chronic pancreatitis with VTE, respectively 29,30 . Our analysis additionally found some moderate associations of gastroesophageal reflux disease, gastritis and duodenitis, irritable bowel syndrome, diverticulum, non‐alcoholic fatty liver disease, and biliary diseases with VTE risk.…”
Section: Discussionsupporting
confidence: 72%
“…8,17,[25][26][27][28] Likewise, two studies identified positive associations of acute and chronic pancreatitis with VTE, respectively. 29,30 Our analysis additionally found some moderate associations of gastroesophageal reflux disease, gastritis and duodenitis, irritable bowel syndrome, diverticulum, non-alcoholic fatty liver disease, and biliary diseases with VTE risk. The association for diverticular disease was found in other studies.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, thromboembolism is more prevalent in necrotizing pancreatitis. In a retrospective cross-sectional study, 7.1% of patients with acute necrotizing pancreatitis had a venous thromboembolic event, whereas only 2.8% of patients with acute non-necrotizing pancreatitis had a venous thromboembolic event [ 6 ]. Moreover, patients with thromboembolism had a higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…The development of NP has been associated with a 2 to 3 times higher rate of deep vein thrombosis and pulmonary embolism, respectively, than acute nonnecrotizing pancreatitis . Standard dosing of unfractionated and low-molecular-weight heparin has been shown to be insufficient in more than 75% of patients with NP, and subprophylactic anti–factor Xa levels in this context were significantly associated with the development of deep vein thrombosis on screening ultrasound examinations …”
Section: Complications During Step-up Managementmentioning
confidence: 99%